Visions of the Irish dream - Quintelli-Neary, Marguerite, 1953- (Cambridge Scholars Pub., 2009)
Visions of the Irish Dream assembles essays that examine the elusive dream of the Irish and Irish Americans, looking at aspirations of 19th-century emigrants to Canada And The United States, political and educational goals of the Irish, historic trauma, contemporary xenophobia, and artists' renditions of "Irishness." Whether the dreams are fulfilled or deferred, they all strive to come to terms with what it means to be Irish; sometimes the definition involves bringing a piece of the old country with you, buying facsimiles of "genuine Irish goods," or redefining self in a way that frees Ireland of the colonial model. This study explores the conflicted and shifting visions of the people who inhabit or have left an isolated island that has moved from a search for independence to integration into a European union. From discussion of the politics of translation in Ferguson and Mangan To The establishment of the National schools, The movement of the Celts from continental Europe as evidenced in Joyce To The translatlantic flight of the Irish To The Americas in a drama by Nicola McCartney, And The re-invention of the feminine force in the writings of novelists Jennifer Johnston and Roddy Doyle To The feminine voice expressed in the work of poet Eilèan NìChuilleanàin, The collection underscores the significance of the dream in Irish history And The arts.